Utilizing the Ellik bladder evacuator during cystoscopic retrieval of urocystoliths in 12 dogs - John Shamoun; Shelly L. Vaden; Allison R. Kendall; Patricia L. Secoura (Journal of Veterinary Internal Medicine)
Abstract Background Urocystolithiasis is a common problem in dogs; many canine uroliths are resistant to medical dissolution. Novel management options would expand, and in some cases improve, current urolith retrieval strategies. Hypothesis/Objectives To describe a previously unreported technique by the Ellik bladder evacuator (EE) to assist in minimally invasive, cystoscopic retrieval of canine cystoliths. Animals Twelve client‐owned dogs presented with urocystolithiasis. Methods In this retrospective study, dog demographics, procedure type and duration, and clinical outcomes of dogs undergoing cystoscopic cystolith retrieval utilizing the EE are described. Results Twelve dogs underwent 13 cystoscopic procedures utilizing EE for cystolith retrieval. The EE was used in accordance with previously described techniques via a custom‐made adaptor. Ten dogs were spayed females; 8 different breeds were represented. In 8 of 13 procedures, transurethral cystoscopy alone by EE with or without wire basket or grasping forceps was performed with a median procedure duration of 36 minutes (range, 16‐52). In the other 5 procedures, additional interventions (ie, laser lithotripsy, percutaneous perineal approach, urethral stricture ballooning, ethanol parathyroid ablation) were performed as indicated with a median procedure duration 110 minutes (range, 42‐144). No complications were noted in association with the use of the EE; retrieval of cystoliths was complete in 12 of 13 procedures. Conclusions and Clinical Importance Use of the EE during cystoscopy might aid in minimally‐invasive retrieval of cystoliths. This work provides a starting point for additional discussion regarding its benefit relative to current interventions.